Isolation and Identification of Endophytic Fungi in Leaves of Jamblang (Syzygium cumini L.) - Suci Hatru Ramadhani; Samingan Samingan; Iswadi Iswadi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Endophytic fungi that live on plant tissue has the potential to produce secondary metabolites, same as its host. This study aimed to identify the types of endophytic fungi found in leaves of Jamblang (Syzygium cumini L.). This study used a qualitative approach and exploration and experimentation method. The sample used in this research was leaves of Jamblang from Ujongbatee, Mesjid Raya sub-district, Aceh Besar. The data were collected with some procedures: (1) isolation using sterilization surface method and (2) identification of endophytic fungi conventionally by observing microscopic and macroscopic morphological phenotypic characters then compared with the monograph. The results showed that endophytic fungi isolated from leaves of Jamblang as many as 11 species have been identified and were as much as 7 types and were grouped into 7 genus: Fusarium, Macrophopmina, Dactylella, Paecilomyces, Nigrospora, Acremonium and Colleotrichum. The types of endophytic fungi that found on immature leaves were Fusarium sp., Isolate I, Paecilomyces sp., Isolate III, Macrophomina sp., and Acremonium sp. Fusarium sp., Macrophomina sp., Paecilomyces sp., Isolate I, and Isolates II have been found in the middle-mature leaves. While in mature leaves, Dactyela sp., Fusarium sp., Nigrospora sp., Acremonium sp., and Colletotrichum sp., Isolate I, Isolate III and IV Isolates were found. Key words: isolation, identification, endophytic fungi, leaves of jamblang